2013
DOI: 10.1186/1475-2840-12-135
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac implications of hypoglycaemia in patients with diabetes – a systematic review

Abstract: BackgroundHypoglycaemia has been associated with increased cardiovascular (CV) risk and mortality in a number of recent multicentre trials, but the mechanistic links driving this association remain ill defined. This review aims to summarize the available data on how hypoglycaemia may affect CV risk in patients with diabetes.MethodsThis was a systematic review of available mechanistic and clinical studies on the relationship between hypoglycaemia and cardiovascular risk. Study outcomes were compiled from releva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(64 citation statements)
references
References 84 publications
2
59
0
3
Order By: Relevance
“…This study could not account for hypoglycemia-associated mechanisms such as release of glucagon and catecholamines (epinephrine), enhanced platelet aggregation, cardiac autonomic neuropathy, or QTc interval changes, which lead to life-threatening cardiac arrhythmias that could explain the increased risk of mortality after a major CVD event in type 1 diabetic patients with histories of severe hypoglycemia (21).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study could not account for hypoglycemia-associated mechanisms such as release of glucagon and catecholamines (epinephrine), enhanced platelet aggregation, cardiac autonomic neuropathy, or QTc interval changes, which lead to life-threatening cardiac arrhythmias that could explain the increased risk of mortality after a major CVD event in type 1 diabetic patients with histories of severe hypoglycemia (21).…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review of cardiac implications of hypoglycemia in patients with diabetes identified only one study of type 2 diabetic patients (ADVANCE) that could determine a clear association between prior severe hypoglycemia and increased risk of death from any cause (HR 2.69 [95% CI 1.97-3.67]) (21). We have estimated a lower association in type 1 diabetes, with an HR of 1.79 (95% CI 1.37-2.35) in the first 28 days after a CVD event and an HR of 1.25 (95% CI 1.02-1.53) after 28 days post CVD event.…”
Section: Discussionmentioning
confidence: 99%
“…A similar relationship between severe hypoglycaemia and the risk of death was shown in both arms (glargine and standard care) of the ORIGIN study evaluating patients with prediabetes or mild T2DM [33]. A systematic review indicates that hypoglycaemia mechanistically contributes to cardiovascular risk by increasing thrombotic tendency, causing abnormal cardiac repolarization, inducing inflammation, and contributing to the development of atherosclerosis and to severe events such as unstable angina, non-fatal and fatal myocardial infarction, sudden death, and stroke in patients with diabetes [34].…”
Section: B) Hyperglycaemia : Minor Role In a Complex Pathophysiology mentioning
confidence: 99%
“…Low blood glucose levels trigger an acute, compensatory catecholamine response which along with a concomitant drop in potassium levels affects cardiac depolarization prolonging the QT interval generating a proarrhythmogenic environment. During sleep, it is likely that exaggerated sympathoadrenal activation, with or without electrolyte disturbances, leads to more lethal ventricular arrhythmias and is thought to be the cause of the so-called 'dead in bed' scenario whereby young T1DM patients are found dead in an undisturbed bed [15,16]. Acute, insulin-induced hypoglycemia has been shown in numerous studies to induce a proinflammatory state.…”
Section: Mechanisms Linking Hypoglycemia and Cardiovascular Diseasementioning
confidence: 99%